Improvement of the mechanizm of information support of companies providing international tourism services - Стоян, Катерина Сергіївна (Technology audit and production reserves, 2013)
Despite the great number of studies on the management of travel agencies providing international tourism services, which are mainly focused on the theoretical aspects of the functioning of the administration, the issues of implementation of practical methods and management tools require special attention. The article concerns the theoretical - methodological aspects of organizational - economic mechanism of tourist operators providing international tourism services, in order to determine its key elements. The main functional subsystems of logistics information system of tourist operators were determined. We have justified the necessity to improve the methodology of logistization of subsystems of logistic information system. We first have proposed the practical tools of introduction to the mechanism of information support, implementation of which increases the effectiveness of strategic management of tourist operators, which provide services for foreign visitors.